Uji Toksisitas Insektisida Nabati Daun Mindi (Melia azedarach L.) Terhadap Hama Kutu Kacang (Callosobruchus maculatus) Pada Penyimpanan - Kholifatunnisa, Fani Sri; Sugiarto, Sugiarto; Afifah, Lutfi (UNIVERSITAS LABUHANBATU, 2024)
The cowpea weevil (Callosobruchus maculatus) is a primary pest of stored legumes. It causes economic losses, necessitating control measures to suppress its population. Typically, synthetic insecticides are used for pest control, but their continuous use can harm the environment. This study aimed to determine the optimal dosage of a botanical insecticide derived from Melia azedarach leaves to enhance its toxicity against the cowpea weevil during green bean storage. The experiment was conducted at the Plant Pest Organism Laboratory, Faculty of Agriculture, UnsikaKarawang. A Completely Randomized Design (CRD) was employed, with treatments including P0 (botanical insecticide 0 g/100 g), P1 (botanical insecticide 15 g/100 g), P2 (botanical insecticide 20 g/100 g), P3 (botanical insecticide 25 g/100 g), P4 (botanical insecticide 30/100 g), P5 (botanical insecticide 35 g/100 g), and P6 (carbosulfan insecticide 2 g/100 g). The treatments were directly applied to green beans. Parameters observed included temperature, humidity, daily mortality, and seed weight loss. The results showed that the 35-gram Melia azedarach leaf insecticide achieved 85% mortality on the 7th day and minimized seed weight loss by 0.15 grams. Thus, the 35-gram botanical insecticide effectively controls the cowpea weevil (Callosobruchus maculatus) and reduces its population. Keywords : callosobruchus maculatus, mortality, seed weight.